Armando Uribe Arce and Floridor Pérez (Second meeting of writers in Chiloé, Castro, 1988) (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
The military dictatorship —referred to today by various euphemisms— from the very first day, led to a forced silencing of Chilean writers. At least in the two years following the coup, little to nothing was known about who was in Chile and who was not. Rumors abounded, "that one is here, that one is in Romania, that another is in Germany or something like that, that nobody knows anything about that other one.” After two or three years of almost complete silence, awakening began, coinciding with the emerging voice of the new generation. Gradually, literary workshops, national poetry competitions, and writers’ meetings (primarily poets) began to be organized in provinces and Santiago. At the same time, the publication of loose sheets, pamphlets, small magazines, and even anthologies began, generally mimeographed. (Document excerpt)